Interactive Web-based radiology teaching file...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in R\diology.' Houston, TX, May 6-9, 1999 - Zaidel M; Hopper K; Iyriboz T (Journal of Digital Imaging)
This multimedia radiology teaching file was developed for medical students, residents, physicians, and researchers to present teaching components related to clinical studies. Patient studies are used to create teaching cases, user can also create lecture series and custom presentations (catalogs) by linking related text and images. The user is able to make and preserve his/her own notes related to reviewed information. From the computer workstation, the user can perform search our case library by American College of Radiology (ACR) codes, keywords, modalities, or text. Results are presented in custom pages and include text lists, thumbnails lists, rescaled images, and full-size images. Text can be easily printed in custom format or exported to an ASCI file. To preserve the privacy of the student, access to our database is granted to the web browser by log-in panel. Image and text can be imported from Digital Imaging and Communications in Medicine (DICOM)-compatible devices or entered by using web forms. In conclusion, we developed a multifunctional interactive teaching environment accessible for multiplatform internet users. Copyright (c) 1999 by W.B. Saunders Company